2021
DOI: 10.1021/acs.jpcb.1c02816
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Weak and Strong Hydrogen Bonds in Liquid Water—A Potential of Mean Force-Based Approach

Abstract: The ability to form hydrogen bonds is one of the most important factors behind water’s many anomalous properties. However, there is still no consensus on the hydrogen bond structure of liquid water, including the average number of hydrogen bonds in liquid water. We use molecular dynamics simulations of the polarizable iAMOEBA water model for investigating the hydrogen bond characteristics of liquid water over a wide range of temperatures and pressures. Geometric definitions of a hydrogen bond often use a recta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 68 publications
7
34
0
Order By: Relevance
“…exhibit geometries similar to that of ice I h (the hexagonal crystalline form of ice). Hydrogen bonds defined by this criterion were also observed 66 to show statistics similar to that of strong hydrogen bonds reported by Wernet et al 9 Therefore, hydrogen bonds that lie in the region PMF ≤ À2 kT were distinguished as "ice-like" or "strong" hydrogen bonds. 66 Interested readers are referred to our previous work for more details.…”
Section: Identifying Hydrogen Bondssupporting
confidence: 68%
See 1 more Smart Citation
“…exhibit geometries similar to that of ice I h (the hexagonal crystalline form of ice). Hydrogen bonds defined by this criterion were also observed 66 to show statistics similar to that of strong hydrogen bonds reported by Wernet et al 9 Therefore, hydrogen bonds that lie in the region PMF ≤ À2 kT were distinguished as "ice-like" or "strong" hydrogen bonds. 66 Interested readers are referred to our previous work for more details.…”
Section: Identifying Hydrogen Bondssupporting
confidence: 68%
“…Here, kT is the magnitude of thermal fluctuations in the system at temperature T. We reported that this region could be well captured by a partial ellipse. 66 This method is also capable of identifying hydrogen bond configurations that lie deeper inside the PMF wells. We showed that hydrogen bonds which lie deeper inside the PMF well (PMF ≤ À2 kT)…”
Section: Identifying Hydrogen Bondsmentioning
confidence: 99%
“…Two molecules are defined to be hydrogen bonded if the oxygen-hydrogen (O-H) distance and the oxygenhydrogen-oxygen (O-H-O) angle lie in the statistically favourable region on the distance-angle plane, defined by PMF ≤ 0 kT. We also reported that a vast majority of hydrogen bonds formed in the ice I h crystal lie in a smaller sub-region on the PMF landscape, defined by PMF ≤ -2 kT [73]. We used these PMF based definitions of hydrogen bonds to compare the tetrahedrally hydrogen bonded fraction of liquid water with the LFTS fractions estimated from other methods.…”
Section: A Estimating the Fraction Of Lftsmentioning
confidence: 90%
“…We also compared the fraction of LFTS molecules estimated by θ avg with the fraction of tetrahedral environments indicated by hydrogen bond formation. In a recent work [73], we used Potential of Mean Force (PMF) landscapes to distinguish 'ice-like' hydrogen bonds in liquid water. Two molecules are defined to be hydrogen bonded if the oxygen-hydrogen (O-H) distance and the oxygenhydrogen-oxygen (O-H-O) angle lie in the statistically favourable region on the distance-angle plane, defined by PMF ≤ 0 kT.…”
Section: A Estimating the Fraction Of Lftsmentioning
confidence: 99%
See 1 more Smart Citation